(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
This study included the experimental production and investigation of the mechanical properties of paving tiles produced from a mixture of laterite, silica sand, pulverized cow bones, and cement. Empirical models of compressive and flexural strength were also developed and herein presented for the paving tiles. The maximum compressive strength of the paving tiles were obtained for 20, 15, and 10% cement content as 5.05, 5.05 and 3.08 MPa, while the maximum flexural strength for similar values of cement content were obtained as 1.83, 1.21 and 0.26 MPa respectively. The results indicate that there was no noticeable difference in the values of the compressive strength at 20 and 15% cement content, while a sharp reduction of the mechanical properties was experienced as the cement content reduces from 15 to 10%. Recommended composition for paving tiles with pulverized cow bones composite is cement, 15%; pulverized cow bones, 30%; laterite 35% and silica sand, 20% respectively. Sustainable production of paving tiles and a sustainable environment can, therefore, be enhanced by replacing granite constituent with waste cow bones, which can easily be replicated by the empirical models herein developed.